The Oxford Ankle Foot Questionnaire for children: responsiveness and longitudinal validity. - Morris, C; Doll, H; Davies, N; Wainwright, A; Theologis, T; Willett, K; Fitzpatrick, R (2009)
PURPOSE: To evaluate how scores from the Oxford Ankle Foot Questionnaire change over time and with treatment using both distribution-based and anchor-based approaches. METHODS: Eighty children aged 5-16 and their parent or career completed questionnaires at orthopaedic or trauma outpatient clinics. They were asked to complete and return a second set of questionnaires again within 2 weeks (retest), and then mailed a third set of questionnaires to complete again after 2 months (follow-up). The follow-up questionnaires included a global rating of change 'transition' item. RESULTS: Child- and parent-reported mean domain scores (Physical, School and Play, and Emotional) were all stable at retest, whereas positive mean changes were observed at follow-up. As we hypothesised, trauma patients had poorer scores than elective patients at baseline, and showed greater improvement at follow-up. For trauma patients, mean changes in per cent scores were large (scores improved between 40 and 56 for the Physical and School and Play domains, and 17 and 21 for Emotional); all effect sizes (ES) were large (>0.8). For elective patients, the mean improvement in per cent scores were more moderate (Physical: child 10, ES = 0.4, parent 11, ES = 0.5; School and Play child 0, ES = 0, parent 9 ES = 0.4; Emotional: child 6, ES = 0.2; parents 8, ES > 0.3). Minimal detectable change (MDC(90)), an indication of measurement error, ranged from 6 to 8. Half the standard deviation of baseline scores ranged from 11 to 18. Minimal important difference could only be calculated for elective patients (9 child and 13 parent ratings), these ranged from 7 to 17. CONCLUSIONS: The findings support the responsiveness and longitudinal validity of the scales. Changes in domain scores of, or exceeding, the MDC(90) (6-8) are likely to be beyond measurement error; further work is required to refine the estimate of change that can be considered important.